Lifestyle politics narratives without full political self-identification: A qualitative study of Italian eco-influ-activists active on Instagram - Baratin, Anna; Setiffi, Francesca (Mediascapes journal, 2024)
This article explores the motivations, beliefs, and self-identification of a qualitative sample of 20 Italian environmental communicators active on Instagram. The analysis of the biographical interviews and the specific focus on the self-categorization of being or not being an activist suggest that we can consider all the sample participants as falling within the category of eco-influ-activists. The majority do not consider themselves “pure” activists, and there are different reasons for this: some narratives can be related to political lifestyle activism, while the “self-identified” science communicators explicitly indicate their need to be recognized as “scientists” and not activists or politicians because they discuss scientific facts and knowledge, and they constantly show the need to be considered as “objective” as possible. The discussion of the results sheds new light on the environmental communicators and their originality based on the following: a) the interpretation of their self-identification as non-activists, and because they debate activists’ and political topics, they can be included in the realm of eco-influ-activism, wherein environmental issues are debated and connected to consumer choices and lifestyles and/or scientific facts, and b) the blurred borders of the private and public spheres and of political and nonpolitical narratives.